Gingival enlargement improvement following medication change from amlodipine to benidipine and periodontal therapy. Issue 5 (19th May 2022) - Kamei, Hidehiko; Furui, Maria; Matsubara, Tatsuaki; Inagaki, Koji
Abstract : The use of calcium channel blockers (CCBs) is associated with gingival enlargement, which adversely affects oral function, hygiene and aesthetics. Although CCB-induced gingival enlargement is a known adverse effect, it is rarely or never caused by some CCBs. In this paper, we report the case of a late 80's female patient with hypertension who experienced amlodipine-induced gingival enlargement. The patient's antihypertensive medication was changed from amlodipine to another CCB of the same class, benidipine, which has not been reported to cause gingival enlargement. The patient also received periodontal therapy. A significant improvement in gingival enlargement was noted, and blood pressure control was maintained. This case indicates that it might be beneficial for patients with hypertension presenting CCB-induced gingival enlargement to switch from the CCB that caused gingival enlargement to another CCB with little to no risk.